2014
DOI: 10.1007/s00167-014-3239-3
|View full text |Cite
|
Sign up to set email alerts
|

Steroid-induced femoral head osteonecrosis in immune thrombocytopenia treatment with osteochondral autograft transplantation

Abstract: Osteonecrosis of the femoral head is a devastating complication of steroid administration and has rarely been observed in the treatment of immune thrombocytopenia. The treatment of osteochondral defects in advanced stages of avascular necrosis (AVN), characterized by collapse of the subchondral bone, remains an unsolved burden in orthopedic surgery. In this report, we present a case of a 19-year-old female that was admitted in the Emergency Department with walking disability and painful hip joint movement due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Given the absence of definite underlying pathogenesis and efficacious therapeutics, steroid-induced avascular necrosis of femoral head (SANFH), a common bony complication of corticosteroid treatment, is causing many patients to suffer from considerable pain and economic losses 2 4 . Recent studies have proven that the pathogenic mechanisms of SANFH are closely correlated with excessive inflammatory immune response 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Given the absence of definite underlying pathogenesis and efficacious therapeutics, steroid-induced avascular necrosis of femoral head (SANFH), a common bony complication of corticosteroid treatment, is causing many patients to suffer from considerable pain and economic losses 2 4 . Recent studies have proven that the pathogenic mechanisms of SANFH are closely correlated with excessive inflammatory immune response 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…As suggested by a Chinese epidemiologic study, SANFH accounts for approximately 24.1% of all cases of osteonecrosis of the femoral head (ONFH) (2). Thus far, the mechanism underlying SANFH has not been not clear (3), but the general consensus is that several pathways may interrupt the bone microcirculation process and affect the supply of essential nutrients. As a result, deaths of both osteocytes and fat cells may occur, resulting in further damage to bone structures (4).…”
Section: Introductionmentioning
confidence: 99%
“…OAT is one of the most common surgical procedures for cartilaginous or osteochondral lesions in the knee, ankle, elbow, and hip joints. 4,5,22 Overall, good or excellent OAT results have been reported for both cartilaginous or osteochondral lesions, although some clinical trials have reported higher revision rates or inferior clinical results compared with the autologous chondrocyte implantation. 1,2 In the systematic review by Pareek et al, 28 the overall failure rate was 28%, and increased patient age, previous surgery, and defect size were correlated with increased risk of failure.…”
Section: Discussionmentioning
confidence: 99%